Agar Plate Method for Detection and Enumeration of Alkylbenzenesulfonate-Degrading Microorganisms - Ohwada, Kouichi (1975)
A simple method for detection and enumeration of alkylbenzenesulfonate (ABS)-degrading microorganisms by using agar plates was developed and used in microbiological studies of coastal marine and polluted river waters. The method depends upon the color responses of neutral red in alkaline medium. Neutral red changes from pink, when it enters into ABS micelles, to yellow, when the ABS is degraded, and does not form micelles. When neutral red-tris(hydroxymethyl)-aminomethane buffer solution and then cationic surfactant solution were sprayed onto the agar surface of ABS-nutrient agar cultures, transparent haloes appeared around the colonies of ABS-degrading microorganisms against a pink background. Viable counts of ABS-degrading bacteria isolated from both seawater and freshwater environments were considerably higher in polluted waters than in less polluted areas. Viable counts of ABS-degrading bacteria averaged 1.5 × 10(5)/ml in samples from the surface water of polluted Tokyo Bay and 3.0 × 10(4)/ml in samples from the surface water of polluted Tamagawa River but were fewer in number in samples from less polluted waters.